Inka and local ceramic production and distribution networks: a view from the Chinchaysuyo and Colesuyo - Baca Marroquín, Ancira Emily (2023)
This paper uses multiple geochemical ceramic datasets generated using Laser Ablation Inductively Coupled Plasma Mass-Spectrometry (LA-ICP-MS) to reconstruct patterns in the manufacture of ceramics in four locales of the Inka realm. Specifically, we compare local and Inka Polychrome styles in different regions of the empire. Collectively, these data reveal that local systems of production were not greatly transformed by imperial expansion. However, our results suggest that potters continued to produce their earlier styles and added Inka styles manufactured with similar raw materials to their repertoire. This indicates that they actively made use of newly introduced craft concepts during political shifts. These results show the adaptability of local ceramicists in experimenting and/or learning paste recipes to manufacture Inka forms and design canons. Additionally, the data highlight the role of potters as participants in Inka imperialism through their manufacture of both foreign pottery and local ceramic styles.